2021
DOI: 10.3390/ijms22168872
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Reverses Disruption of Gut Epithelial Barrier Function Caused by Campylobacter jejuni

Abstract: Infections by the zoonotic foodborne bacterium Campylobacter jejuni (C. jejuni) are among the most frequent causes of bacterial gastroenteritis worldwide. The aim was to evaluate the relationship between epithelial barrier disruption, mucosal immune activation, and vitamin D (VD) treatment during C. jejuni infection, using intestinal epithelial cells and mouse models focused on the interaction of C. jejuni with the VD signaling pathway and VD treatment to improve C. jejuni-induced barrier dysfunction. Our RNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…They did not show an anti-microbial effect, but rather an immunomodulatory and barrier-stabilizing effect, such as the polyphenols curcumin or resveratrol or the hormone vitamin D (calcitriol) [ 6 , 7 , 8 ]. In addition, vitamin D has been reported to protect against macromolecule influx into C. jejuni -infected intestinal epithelial cells and against bacterial translocation [ 8 ]. However, their exact molecular influence on transcytotic processes in the intestinal epithelium has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They did not show an anti-microbial effect, but rather an immunomodulatory and barrier-stabilizing effect, such as the polyphenols curcumin or resveratrol or the hormone vitamin D (calcitriol) [ 6 , 7 , 8 ]. In addition, vitamin D has been reported to protect against macromolecule influx into C. jejuni -infected intestinal epithelial cells and against bacterial translocation [ 8 ]. However, their exact molecular influence on transcytotic processes in the intestinal epithelium has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Natural compounds have been identified that may combat C. jejuni infection by enhancing barrier function and down-regulating immune activation, namely the polyphenols resveratrol and curcumin, and the pre-hormone vitamin D [ 6 , 7 , 8 ]. Complementary intervention strategies of this type are conceivable for acute infections, but could also be useful for oral use in the recovery phase of an infection or afterwards for the prevention of PI-IBS.…”
Section: Introductionmentioning
confidence: 99%
“…Several infection-induced immune mediators, such as tumor necrosis factor (TNF), IL-6, IL-8, IL-12, IL-23 and IL-1β, intensify the barrier damage as discussed below. They also intensify diarrhea, as characterized by sodium malabsorption through dysregulation of the sodium channel ENaC [ 73 ]. Recent studies in cell culture in vitro and in mice in vivo indicated a significant reduction of C. jejuni -triggered epithelial barrier dysfunction by application of the polyphenol curcumin [ 74 ] or vitamin D [ 73 ].…”
Section: Pathogenesis Of Campylobacter Infection A...mentioning
confidence: 99%
“…The depletion of the murine gut microbiota by antibiotic pretreatment facilitated establishment of the enteropathogens alongside the gastrointestinal tract, whereas the il-10 gene knockout rendered mice susceptible to bacterial LOS resulting in clinical signs and immune-pathological responses upon oral C. jejuni infection as seen in human campylobacteriosis ( Mousavi et al, 2020a ). This C. jejuni infection and inflammation model has already been validated on numerous compounds, such as vitamins ( Mousavi et al, 2020b ; Lobo de Sá et al, 2021a ), plant derived biomolecules ( Mousavi et al, 2020c , d ), essential oils ( Bereswill et al, 2021a ; Heimesaat et al, 2021 ; Mousavi et al, 2021 ), activated charcoal ( Bereswill et al, 2021b ) as well as the short chain fatty acid butyrate ( Du et al, 2022 ), in order to assess their anti-microbial and immunomodulatory properties in acute campylobacteriosis.…”
Section: Introductionmentioning
confidence: 99%